2021
DOI: 10.1371/journal.pone.0256005
|View full text |Cite
|
Sign up to set email alerts
|

Above-ground carbon stock and REDD+ opportunities of community-managed forests in northern Thailand

Abstract: This study aimed to investigate the structure of two deciduous forests and assess their above-ground carbon stock in order to promote community forest management (CFM) for REDD+ opportunities in the Ban Mae Chiang Rai Lum Community Forest in northern Thailand. A systematic sampling method was used to establish twenty-five sample plots of 40 m × 40 m (0.16 ha) each that were used to survey the entire 3,925 ha area of the community forest. Cluster analysis identified two different forest types: dry dipterocarp f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…However, this study also found that engagement in decision making was at a 'moderate' level, suggesting that it had a limited impact on species conservation and utilization (Figure 7). In analyzing the same area as this study, found that the rate of above-ground carbon sequestration would decrease from 2028-2038 under CFM when compared with the previous decade [109]. This highlights the importance of a long-term focus on all aspects of management participation to maximize the positive impact on ecosystem services for the sustained viability of the forest and its resources.…”
Section: Impact Of Cfm On Ecosystem Servicesmentioning
confidence: 55%
See 1 more Smart Citation
“…However, this study also found that engagement in decision making was at a 'moderate' level, suggesting that it had a limited impact on species conservation and utilization (Figure 7). In analyzing the same area as this study, found that the rate of above-ground carbon sequestration would decrease from 2028-2038 under CFM when compared with the previous decade [109]. This highlights the importance of a long-term focus on all aspects of management participation to maximize the positive impact on ecosystem services for the sustained viability of the forest and its resources.…”
Section: Impact Of Cfm On Ecosystem Servicesmentioning
confidence: 55%
“…Collaborative management efforts between the government and local residents became more focused on forest plantations, fire protection and patrol, and the utilization of check dams. As a result, the community forest showed signs of restoration, and the damage caused by years of deforestation and degradation has been mitigated [109]. Plant density, growth rates, and the regeneration of plant species in the community forest increased in the study area under CFM.…”
Section: Participation In Cfm and Satisfaction With Ecosystem Servicesmentioning
confidence: 95%
“…Mixed deciduous forests (MDFs) are a type of tropical deciduous forest that comprises approximately 18.26% of Thailand's forest cover (Thammanu et al 2021). These forests exhibit considerable variation in their composition and structure, in uenced by a range of climatic and edaphic factors (Marod et al 1999;Baker and Bunyavejchewin 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thailand is one of the countries with the most abundant forest resources in Southeast Asia. Forests occupy 31.64% of the country's area (Thammanu et al 2021). The western part of the country occupies 19.67% of the total forest area, which dominantly occur in Ratchaburi, Phetchaburi, and Kanchanaburi Province.…”
Section: Introductionmentioning
confidence: 99%